2018
DOI: 10.3171/2016.11.jns161871
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors governing the development of cerebral vein and dural sinus thrombosis after craniotomy in patients with intracranial tumors

Abstract: OBJECTIVE Neurosurgical intervention may increase the risk of developing cerebral vein and dural sinus thrombosis (CVT). The clinical management of CVT in postoperative patients remains unclear. This retrospective study explores the disease occurrence, associated risk factors, and outcomes in patients with tumors who developed CVT after craniotomy. METHODS A retrospective analysis and review of patient records in those who had undergone cranial tumor removal within the authors' neurosurgical department was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
(39 reference statements)
0
25
0
Order By: Relevance
“…The authors found an overall CVT incidence of 1.53% among 2,286 reviewed charts. A multivariate analysis identified age >55 years old, semisitting position (OR 7.55, 95% CI 3.73-15.31, p < 0.001) and other known comorbidities as the main risk factors for CVT (28,29,34).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found an overall CVT incidence of 1.53% among 2,286 reviewed charts. A multivariate analysis identified age >55 years old, semisitting position (OR 7.55, 95% CI 3.73-15.31, p < 0.001) and other known comorbidities as the main risk factors for CVT (28,29,34).…”
Section: Discussionmentioning
confidence: 99%
“…Many papers have reported the safety and diagnostic value of materials obtained using stereotactic biopsy [46][47][48][49][50]. The number of perioperative complications occurring during surgical resections of brain tumours remains significant [51]. Even in our neurosurgery department, a facility with a high level of experience, the performance status decreased in two out of 11 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses should monitor for CSF leakage at the surgical site; if clear fluid drainage at the site is found, they should notify the surgeon. Bleeding or vascular injury can occur if ancillary vascular structures are affected by the tumor . Damage to ancillary brain structures, including cerebral contusion or infarction, can occur after the extradural retraction of the brain during the procedure …”
Section: Perioperative Carementioning
confidence: 99%